Pemanfaatan LMS (Learning Manajemen System) Dalam Pembelajaran Mata Kuliah Dasar Umum (MKDU) Di Perguruan Tinggi - Hendy Satria; Sary Sukawati (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
It cannot be denied that problems can arise due to changes in learning platforms, especially if the LMS used is still new for students. The aim of this research is to determine the design of using LMS in MKDU learning in higher education as well as student responses to the use of LMS. The research method uses descriptive qualitative. The research objects are LMS and STIKES Jendral Achmad Yani students who contracted for Citizenship and Indonesian Language Education in the first semester. Data collection techniques use observation techniques and questionnaire techniques. Data will be analyzed descriptively qualitatively. The research results show that the design for using LMS in learning is complete. LMS facilitates several features including: RPS upload, material upload, chat/discussion feature, attendance list, and assessment. The results of the student questionnaire regarding the use of LMS in courses showed a positive response. It can be concluded that the use of LMS in MKDU learning is in the good category